Wrist Arthroscopy - Geissler, William B.; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
Dr. William B. Geissler has selected an international group of experts to compose this practical guide to wrist arthroscopy that is a comprehensive reference for both orthopedic residents new to the field and for experienced orthopedic surgeons looking to refine their technique. The book covers fundamental topics, such as arthroscopic anatomy and the proper evaluation of wrist pain, before advancing to thorough discussions of electrothermal shrinkage, arthroscopy of the thumb and small joints of the hand, and specific diagnoses for an array of common injuries. Orthopedists will appreciate the emphasis that this book places on the treatment of wrist disorders. Current minimally invasive procedures are described in detail, including management of carpal instability, new techniques in arthroscopic repair of TFCC tears, and arthroscopic excision of both volar and dorsal wrist ganglia. Tips and tricks are highlighted that make implementing new techniques easier. The depth of knowledge and attention to detail found in this book reflect Dr. Geissler$1 (Bs dedication to teaching others. In the foreword, Dr. Terry L. Whipple, a pioneer in wrist arthroscopy, notes that the text is an excellent user-friendly resource. Orthopedists looking to master the latest techniques in arthroscopic wrist surgery will find it invaluable.s
General Anatomy and Setup -- Arthroscopic Wrist Anatomy -- Evaluation of the Painful Wrist -- Lasers and Electrothermal Devices -- Repair and Treatment of TFCC Injury -- Repair of Peripheral Ulnar TFCC Tears -- Repair of Peripheral Radial TFCC Tears -- Management of Type C TFCC Tears -- Debridement of Central TFCC Tears -- Arthroscopic Management of Ulnar Impaction Syndrome -- Kinematics and Pathophysiology of Carpal Instability -- Management of Scapholunate Instability -- Management of Lunotriquetral Instability -- Management of Distal Radial Fractures -- Fixation of Acute and Selected Nonunion Scaphoid Fractures -- Management of Articular Cartilage Defects -- Radial Styloidectomy -- Excision of Dorsal Wrist Ganglia -- Wrist Arthrolysis -- Small-Joint Arthroscopy in the Hand and Wrist -- Proximal Row Carpectomy -- Trapeziectomy with Thermal Capsular Modification -- Resection of Volar Ganglia -- Clinical Approach to the Painful Wrist.
Keywords: Medicine; Orthopedics; Sports medicine; Medicine & Public Health; Orthopedics; Conservative Orthopedics; Surgical Orthopedics; Sports Medicine; Electronic books